Challenges in overcoming advanced-stage or relapsed refractory extranodal NK/T-cell lymphoma: meta-analysis of individual patient data - Kim, Tong Yoon; Kim, Tae Jung; Han, Eun Ji; Min, Gi June; Jeon, Youngwoo; Cho, Seok-Goo (Frontiers in Oncology, 2024)
Introduction Extranodal NK/T-cell lymphoma (ENKTCL), a non-Hodgkin lymphoma, is known for its destructive local impact on nasal structures and systemic induction of inflammatory cytokines. Concurrent treatment with radiation and nonanthracycline- based chemotherapy has improved survival rates in patients with localized disease stages. However, survival outcomes vary significantly in advanced-stage and relapsed or refractory (R/R) cases. Methods Therefore, we conducted a meta-analysis using random effects models to assess prognostic factors in advanced or R/R ENKTCL, employing a digital extractor on Kaplan–Meier graphs owing to the scarcity of published prospective trials for these patients. Results We observed that patients with advanced ENKTCL treated with Lasparaginase had a median progression-free survival (PFS) of 14.3 months and an overall survival (OS) of 19 months. In R/R ENKTCL, PFS and OS were 11.7 and 15.6 months, respectively. Additionally, OS outcomes in advanced-stage ENKTCL were better in the asparaginase group than that in the non-asparaginase group, with PEG-asparaginase showing superior results compared with that using Lasparaginase. Epstein–Barr Virus (EBV)-DNA positivity in the bloodstream prior to treatment was associated with poor outcomes in advanced-stage ENKTCL, and similar trends were observed in patients with R/R ENKTCL and post-treatment EBV viremia. Discussion Collectively, these findings suggest that chemotherapy with Lasparaginase or PEG-asparaginase can enhance survival in advanced or R/R ENKTCL. However, future strategies must be developed to effectively suppress EBV viremia and achieve a deep response toward tumor eradication.